Species dynamics and establishment of silviculture agroforestry regime at Southern Gunung Merapi National Park, Java, Indonesia - Suryanto, Priyono (2011)
Gunung Merapi National Park (GMNP) which was established in 2004, as a new management for Merapi forest, has a long historical relationship with the local community. Notably, the pattern of relationship between the GMNP management and the local community is still a paradoxical situation. The existing intervention by local community is through harvesting the grass in the national park areas and this activity is perceived as a lose-win situation. On the other hand, in the perspective of formal legal Indonesian national park principle which introduces the renewal of zonation system that prohibits the local community to harvest grass in GMNP is viewed as a win-lose situation. This study is aimed to develop silviculture agroforestry regime (SAR) model based on synergized agroforestry systems outside national park that are compatible with forest rehabilitation and renewal zonation in GMNP. SAR also supported the basic information on the succession of Mount Merapi following the eruption in 2006 to strengthen the Merapi lava tour.The study was carried out in GMNP, Sleman district, Yogyakarta, Indonesia with the establishment of five (5) permanent sample plots to identify species diversity, species dynamic and potential standing stock of Acacia decurrens post Merapi eruption. Assessment of typology agroforestry was carried out in Kaliadem and Jambu Village with clustering approach. Local community intervention and scheme for forest rehabilitation were based on the index intervention and allometric model. SAR was developed by compatible management between typology agroforestry best practices and the scheme of the forest rehabilitation and renewal zonation system on GMNP as well as supported succession information. The exploring potential of SAR employed the SWOT analysis (i.e. strength, weakness, opportunity and threat), synergized with the Analytic Hierarchy Process (AHP) approach to quantify the potential of the regime.The species that have the ability to grow on the early successional stage after Merapi eruption in 2006 are limited. Based on the importance of value index (IVI) analysis, all the plots were dominated by A. decurrens. Some species recorded IVI values of more than 10%, i.e. the species were A. decurrens, A. villosa, Cinchona rebbeca, Erythrina hypaporus, Euphorbia ciacembus, Ficus kubeba, Psidium guajava, Palotus sp, Pinus merkusii, Schima wallichii and Trema sp. A. decurrens recorded the highest trend of species recruitment and mortality in P1 and P2, while in P3 and P4 were A. decurrens and P. merkusii. In P5, the trend of species mortality was dominated by P. merkusii and A. villosa, while the recruitment species was dominated by S. wallichii and A. villosa. The performance of A. decurrens based on the highest average values of diameter and height were 14.22±1.85 cm and 5.97±0.66 m, respectively. Based on density, the average of the highest density was 23965.22±4553.39 individuals/ha, while the lowest was 330.44±69.31 individuals/ha. The standing stock of A. decurrens based on the basal area also showed that P1 had the highest basal area, i.e. 72.07±18.51 m2/ha, while the lowest was found in P2, i.e. 0.45±0.08 m2/ha. Based on volume, P4 was the highest, i.e. 184.44±24.59 m3/ha, while the lowest was found in P2, i.e. 1.11±0.18 m3/ha. There are five SAR models, which are appropriate for agroforestry cluster (AF) i.e. AF1-SAR1, AF2-SAR2, AF3-SAR3, AF4-SAR4 and AF5-SAR5. SAR 1 to SAR 5 have the ability to balance agroforestry management with decreasing local community intervention and increasing biodiversity level on GMNP. The ratio of grass productivity outside GMNP with the implementation of SAR is close to optimum point of one (1). The ratio values of SAR 1 to SAR 5 are 0.982, 1.010, 1.44, 1.047 and 1.253, respectively. SAR has a high potential to be implemented in GMNP as a compatible management approach. In accordance with the stakeholders’ perception, the strengths and opportunities outweigh the model’s weaknesses and threats. In addition, SAR is of immense potential for encouraging prospective buffer zone with intensive agroforestry management and also for accelerating forest rehabilitation and renewal zoning system of GMNP. SAR is also a prospect an innovation of collaborative management in the national park, whereby it does not only maintain the biodiversity, but also enhance the wealth of the poor. Nonetheless, the implementation of SAR must be integrated with various strategies, for instance, the capacity building, documentation process and outcome, participative monitoring and evaluation, backup policy, experimental plot, compensation programme and skill improvement of silviculture agroforestry. Hence, SAR is a compatible management model between the GMNP and the local community - serving as a “window opportunity” for learning model that includes the reference outside the national park as a promising buffer zone for developing this new Indonesia’s national park, which avoids the image of “paper park”.